PENGEMBANGAN ALAT PERAGA SEBAGAI MEDIA PEMBELAJARAN PENERAPAN KONSEP HUKUM PASCAL UNTUK PESERTA DIDIK KELAS VIII DI SMP NEGERI 1 SITIMSEL - Rini Pangke; Jeane Cornelda Rende; Alfrits Komansilan (Charm Sains: Jurnal Pendidikan Fisika, 2021)
Learning media in the form of teaching aids is very important in the physics learning process, as learning with teaching aids can help students more easily understand the concepts under study. The aim of this study was to develop teaching materials as a learning medium for the application of the Pascal law concept for class VIII students at SMP Negeri 1 Sitimsel and to examine the effectiveness of teaching materials as a learning medium for the application of the Pascal law concept for class VIII students at SMP Negeri 1 sitimsel. This type of research is research and development (R&D) according to Sugiyono and the research topics are 5 students in class VIII A and 21 students in class VIII B. The results of the research show the process of developing teaching materials as a learning medium including potential and Problem analysis, design product, design validation, revised design, first attempts, product attempts, use attempts, product revisions and mass production as well as the effectiveness of teaching materials as a learning medium for the application of Pascal's legal concepts for pupils of class VIII at SMP Negeri 1 Sitimsel, from the results shown normalized reinforcement test analysis in the small group test of 0.9 and large group test of 0.92, this is included in the high criteria, so the props are effective in enhancing students' conceptual understanding.